O Buddha e o extremo oriental das Américas: um estudo etnográfico das práticas budistas no estado da Paraíba. - Schenkel, Klara Maria (2013)
This paper is a research proposal of recent insertion of Buddhism (eminently Eastern belief) in northeastern Brazil, specifically in the state of Paraíba (region of predominant Christian tradition). At first, we discuss the means that enable this insertion, as well as the people involved in the process of diffusion of a exotic" religion in the historical and cultural context of Paraiba. Secondly, the focus of this research is the process of translation (or "reframing") of the Buddhist ideals made by the belief system of its original paraibanos practitioners. Our hypothesis is that some of the Buddhist philosophical assumptions can be "read" in the light of Franciscan Christianity. If the discourses are essentially heterogeneous and polyphonic, then Buddhist doctrine when expanded in to the world, inevitably suffered interventions, additions and revisions. Therefore, our objective is to understand, beyond the manners, the process through which, from certain historical conditions, various discursive formations operate in the production of a "new" religious discourse in our region.